2006
DOI: 10.2224/sbp.2006.34.9.1101
|View full text |Cite
|
Sign up to set email alerts
|

Cross-Cultural Validation of Measures of Traumatic Symptoms in Groups of Asylum Seekers From Chechnya, Afghanistan, and West Africa

Abstract: Internal consistencies and convergent validities of (a) the Hopkins Symptom Checklist-25 (HSCL-25; Mollica, Wyshak, deMarneffe, Khuon, & Lavelle, 1987), (b) the Harvard Trauma Questionnaire (HTQ; Mollica et al., 1992), (c) the Impact of Event Scale (IES-R; Weiss & Marmar, 1997), (d) the Bradford Somatic Inventory (BSI; Mumford et al., 1991), (e) the Clinician Administered PTSD Scale (CAPS-1; Blake et al., 1990), and (f) the Social Adaptation Self-Evaluation Scale (SASS; Bosc, Dubini, & Polin, 1997… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
55
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(57 citation statements)
references
References 15 publications
2
55
0
Order By: Relevance
“…The CAPS has stricter diagnostic criteria for PTSD than the other measures and has been validated cross-culturally as a robust measure of PTSD [29,30]. The instruments were interpreted from English into Kinyarwanda, an official language of Rwanda, with the help of 5 students of English interpreting at the National University of Rwanda.…”
Section: Methodsmentioning
confidence: 99%
“…The CAPS has stricter diagnostic criteria for PTSD than the other measures and has been validated cross-culturally as a robust measure of PTSD [29,30]. The instruments were interpreted from English into Kinyarwanda, an official language of Rwanda, with the help of 5 students of English interpreting at the National University of Rwanda.…”
Section: Methodsmentioning
confidence: 99%
“…Validated versions of the MADRS [31,48] and the BDI [23,29] exist in German as well as in Turkish. Regarding the BSI, a German version has been validated in several cultural populations [46] but a Turkish version had to be generated by the authors. The inventory was translated into Turkish by MÇ B, a back translation into German for validity control was performed by a non-member of the study group.…”
Section: Assessmentsmentioning
confidence: 99%
“…Symptoms of PTSD were assessed with a Tibetan version of the Harvard Trauma Questionnaire (HTQ; Mollica et al, 1992), also developed by Lhewa et al (2007). The HTQ has demonstrated excellent statistical properties in a number of refugee studies (Hollifield et al, 2002;Renner, Salem, & Ottomeyer, 2006) and is considered the best-supported measure of PTSD for refugee populations (Hollifield et al, 2002). Lhewa et al found high internal consistency (α = .89) for their Tibetan translation of the HTQ and excellent specificity (.93), but poor sensitivity (.33), in part due to the low frequency of PTSD diagnoses in their sample.…”
Section: E T H O D Participantsmentioning
confidence: 99%